Thigh, gluteal region, and knee joint - Shaw, Hannah (Henry Stewart Talks, 2023)
Lower limb function, Bones of the hip, thigh, and knee, Muscles of the gluteal region, Nerves of the gluteal region, Muscles of the thigh region, Femoral triangle, Nerves and vessels of the thigh region, Knee joint, Menisci